USING CONVERSATION WEBSITES FOR IMPROVING INTERCULTURAL EXCHANGE AND MAINTAIN INTERPERSONAL RELATIONSHIPS OF UNIVERSITY STUDENTS IN EDUCATION 4.0 - Septiana, Dita; Nurhadianti, Nurhadianti; Purwati, Dinar; Murwantono, Didik (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2020)
The reality of education 4.0 is undeniably true of contemporary higher education systems. This is demonstrated by technological developments and online-based developments. This phenomenon is a challenge of any kind, particularly for students to adapt to the creation of learning processes. Therefore, the purpose of this paper is to explore the students ' improvements in their communication exchange skills and establish interpersonal relationship skills through the use of conversation exchange websites. There were six females and four males of students that has been using conversation exchange from some countries taken as participants. This survey was carried out using the video call feature in the Application tool. The semi-structured interview was used to obtain information from students on the specific theme of fun and easy conversation exchange in foreign language communication as a part of the educational challenge 4.0. By using the structural analysis, ten students have fully agreed to the use of a conversation exchange website to improve foreign language communication skills. All males and females were 90% willing to use the conversation exchange website as a measure of the effects of the use of conversation exchange through semi-structured interviews with three questions. The results show that the students ' attitudes have been welcomed by the conversation exchange website to enhance their communication skills in foreign languages. Therefore, the use of conversation exchange should be widely introduced to increase the ability to communicate in a foreign language.